Pengaruh Penambahan Ampas Virgin Coconut Oil dalam Ransum terhadap Performan dan Produksi Karkas Ayam Broiler (The Effect of Virgin Coconut Oil Waste in the Diet of Broiler Chicken on the Performance and Carcass Production) - Dina Oktaviana; Zuprizal (Zuprizal); Edi Suryanto (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The experiment was conducted to examine the effect of addition of Virgin Coconut Oil (VCO) waste on the performance and production of broiler carcass. One hundred and twenty five broiler were divided into 5 treatment groups which were R-O (basal diet), R-0.5 containing (0.5% VCO waste), R-1.0 (1.0% VCO waste), R-1.5 (1.5% VCO waste) and R-2.0 (2.0% VCO waste). Each treatments had 5 replications of 5 birds each. The birds were raised for 5 weeks. At the end of experiment, data of production performance such as weight gain, total intake, and feed conversion were taken. The data were analyzed by using Completely Randomized Design (CRD) with one way analysis. The difference among treatments were tested using Duncan’s new Multiple Range Test (DMRT). The statistical analysis result showed that the addition of VCO waste at level up to 2.0 % did not affect the production performance, carcass weight and carcass percentage. The addition of VCO waste up to level 2.0% increased body weight (P<0.05) and affected the weight and percentage of abdominal fat (P<0.05)(Key words: Broiler chicken, VCO waste, Performance, and Carcass production)